Normal birth belief levels of pregnants and affecting factors - Hacer Unver; Cigdem Karakayali Ay; Zeliha Ozsahi̇n (Medicine Science, 2022)
This study was carried out to determine the normal birth belief levels of pregnant women and the affecting factors. This descriptive study was conducted between November and December 2021 in a pregnant education class of a public university. The sample of the study consisted of 342 pregnant women. Data were obtained through the "Personal Information Form" and "The Belief Scale for Normal Delivery (BSND)". Pregnant women with a mean age of 28.18±4.77 were determined that 75.5% of them were high school and university graduates, 77.8% were not working, 71.1% perceived their economic status as moderate, and 80.7% had a nuclear family structure. In the study, the mean total score of BSND was 77.74±14.91, and it was determined that 12.6% of the pregnant women had low, 62.3% moderate, and 25.1% high-level normal birth beliefs. In this study, it was determined that the level of belief in normal birth during pregnancy was affected by family structure, spouse's employment status, planned pregnancy, choice of birth method, the person who is influential in deciding the mode of birth and receiving training on preparation for birth (p [Med-Science 2022; 11(4.000): 1521-6]